The effect of soaking stainless steel orthodontics bracket with robusta coffee (coffea canephora) on the release of fe ions - Rafael Juan Irwantoro; Himawan Halim (Jurnal Kedokteran Gigi Terpadu, 2023)
Introduction: Robusta coffee (Coffea canephora) is one of the most produced and popular types of coffee in Indonesia. Robusta coffee is included as an acidic beverage because it has an average pH of 5.6 which can increase corrosion. Stainless steel orthodontic bracket is a type of orthodontic bracket that has more resistance to corrosion, however, exposure to stainless steel orthodontic bracket by robusta coffee (Coffea canephora) which has an average pH of 5.6 can increase the corrosion process so that more Fe ions are released. Objective: To determine the effect of soaking stainless steel orthodontic bracket with robusta coffee (Coffea canephora) on increasing the release of Fe ions Methods: Laboratory experiment with post test only control group design. The experiment was divided into two groups, namely the control and treatment groups. In the control group there were 16 stainless steel orthodontic brackets which were soaked in 20 ml of artificial saliva in an incubator at 370C for 24 hours. In the treatment group there were 16 stainless steel orthodontic brackets soaked in 10 ml of artificial saliva and 10 ml of robusta coffee (Coffea canephora) in an incubator at 370C for 24 hours. After that, a test was carried out using AAS tool to see the release of Fe ions contained in the test solution. Results: Robusta coffee (Coffea canephora) increases the release of Fe ions in stainless steel orthodontic brackets. In the treatment group that were soaked in robusta coffee, there was an average of 7.96 ppm of Fe ions released, while in the control group only 4.07 ppm of Fe ions were released. Conclusion: Robusta coffee (Coffea canephora) has been shown to increase the release of Fe ions on stainless steel orthodontic brackets